Criticism of The Methods Of Interpretation Yusuf Al-Qardawi Against The Hadith Rukyat Hilal - Abdul Mufid (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2020)
Abstract The main source for Muslims in understanding Islamic teachings is the Koran and Hadith. For Muslims, the Hadith second ranks after the Koran. Throughout Islamic history, hadith is a source of controversy in Islamic law. Among the problems that are still warm and almost always occur today is an understanding of the observations of the crescent related to the determination of the beginning of the Islamic month. Questioning about the differences in determining the beginning of the Hijri month is the result of different perspectives to understand the hadith about crescent observations. Therefore, the method of understanding the hadith about "crescent observation" is very urgent to be investigated more deeply. The conclusion of this literature-based research process can be seen that the impact of Yusuf al-Qaradawi's understanding of the Hilal rukyat traditions of Hilal is al-Qaradawi's hope to unite fasting and Eid al-Fitr in Europe based on priorities, not unifying all Muslims in the hemisphere of the earth. Keywords: Al-Qaradawi, Hadith, Observation. Abstrak Sumber utama bagi umat Islam dalam memahami ajaran Islam adalah Alquran dan Hadis. Bagi umat Islam, hadis menduduki peringkat kedua setelah Alquran. Sepanjang sejarah Islam, hadis merupakan sumber kontroversi dalam hukum Islam. di antara masalah yang masih hangat dan hampir sering terjadi saat ini adalah pemahaman tentang observasi bulan sabit terkait penentuan awal bulan Hijriah. Menyoal tentang perbedaan dalam menentukan awal bulan Hijriah adalah hasil dari perspektif yang berbeda untuk memahami hadis tentang pengamatan bulan sabit. Oleh karena itu, metode memahami hadis tentang "pengamatan bulan sabit" sangat mendesak untuk diteliti secara lebih mendalam. Kesimpulan akhir dari proses penelitian berbasis kepustakaan ini dapat dilihat bahwa dampak dari pemahaman Yusuf al-Qaradawi terhadap hadis-hadis rukyat hilal Hilal adalah harapan al-Qaradawi untuk menyatukan puasa dan idul fitri di Eropa atas dasar prioritas, bukan menyatukan semua Muslim di belahan muka bumi. Kata kunci : Al-Qaradawi, Hadis, Observasi.